Optimization of GDMT for patients with heart failure and reduced ejection fraction: can physiological and biological barriers explain the gaps in adherence to heart failure guidelines? - Marilyne Jarjour; Anique Ducharme (BioExcel Publishing Ltd, 2023)
Heart failure is a growing epidemic with high mortality rates and recurrent hospital admissions that creates a burden on affected individuals, their caregivers and the whole healthcare system. Throughout the years, many randomized trials have established the effectiveness of several pharmacological therapies and electrophysiological devices to reduce hospitalizations and improve quality of life and survival, mostly for patients with heart failure with reduced ejection fraction (HFrEF). These studies led to the publication of national societies' recommendations to guide clinicians in the management of HFrEF. Yet, many reports have shown significant care gaps in adherence to these recommendations in clinical practice, highlighting suboptimal use and/or dosing of evidence-based therapies. Adherence to guidelines has been shown to be associated with the best prognosis in HFrEF, with patients presenting with intolerances or contraindications having the highest risk of events; however, it remains unclear whether this association is causal or merely a marker of more advanced disease. Furthermore, individual characteristics may limit the possibility of reaching the targeted dosage of specific agents. Herein, we provide a comprehensive overview of clinicians' adherence to heart failure guidelines in a specialized real-life setting, particularly regarding use and optimization of guideline-derived medical therapies, as well as the implementation of more recent agents such as sacubitril/valsartan and SGLT2 inhibitors. We seek potential explanations for suboptimal treatment and its impact on patient outcomes.